2019
DOI: 10.1039/c9nr01103j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the photocatalytic activity of ZnSn(OH)6 achieved by gradual sulfur doping tactics

Abstract: A gradual sulfur doping strategy was first proposed here to expand the optical absorption range, improve the separation efficiency of photogenerated electron–hole pairs, and finally enhance the photocatalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…However, its wide bandgap (~ 3.7 eV) remains the key challenge for the wide-spread use of ZnSn(OH) 6 in visible light [15]. Therefore, several methods have been performed to reduce the bandgap, including the combination with noble metals (Au, Ag, Cu), metal oxides (ZnO, SnO 2 ) [12,19,20], and non-metals (C, S) [21,22]. The metal decoration is one of the best ways to signi cantly enhance the photocatalytic performance for NO x gas removal through the surface plasmon resonance (SPR) effect [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, its wide bandgap (~ 3.7 eV) remains the key challenge for the wide-spread use of ZnSn(OH) 6 in visible light [15]. Therefore, several methods have been performed to reduce the bandgap, including the combination with noble metals (Au, Ag, Cu), metal oxides (ZnO, SnO 2 ) [12,19,20], and non-metals (C, S) [21,22]. The metal decoration is one of the best ways to signi cantly enhance the photocatalytic performance for NO x gas removal through the surface plasmon resonance (SPR) effect [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, from other previous works, it can be found that, after S doping via similar methods, the crystal structure is almost retained. 30,31 Moreover, in those works, the diffraction peaks of S-doped materials all tend to move to lower angles because of the fact that the larger covalent radius of an S atom enlarges the interlayer distance of S-doped materials. 30,31 Moreover, the standard ZnS (JCPDS 23-0677) and SnS 2 (JCPDS 05-0566) phases are shown in Figure S1, and we can see that, after washing with water several times, no obvious peaks due to impurities via sulfurization are present.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although S-doped metal oxide semiconductors have been studied for decades, the S-doping ratio is still very low in most reports ( A s < 10 atom %). To some extent, the low concentration of S hinders the further application of S-doped metal oxide semiconductors in the field of photocatalysis. In our work, we successfully synthesize S-doped ZnSnO 3 with a high S-doping ratio ( ), which is highest among all of the reports about S doping in metal oxide semiconductors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations